2022
DOI: 10.1177/0271678x221083471
|View full text |Cite
|
Sign up to set email alerts
|

Using arterial spin labeling to measure cerebrovascular reactivity in Moyamoya disease: Insights from simultaneous PET/MRI

Abstract: Cerebrovascular reactivity (CVR) reflects the CBF change to meet different physiological demands. The reference CVR technique is PET imaging with vasodilators but is inaccessible to most patients. DSC can measure transit time to evaluate patients suspected of stroke, but the use of gadolinium may cause side-effects. Arterial spin labeling (ASL) is a non-invasive MRI technique for CBF measurements. Here, we investigate the effectiveness of ASL with single and multiple post labeling delays (PLD) to replace PET a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 69 publications
(95 reference statements)
3
28
0
Order By: Relevance
“…In this study, we encoded seven different PLD times with the application of seven effective label durations. Many studies on cerebrovascular disease have utilized multi-delay ASL approaches to correct CBF values for arrival time [56][57][58]. It was demonstrated that the multi-delay ASL technique holds an advantage for clinical applications, particularly for patients with arterial transit time abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we encoded seven different PLD times with the application of seven effective label durations. Many studies on cerebrovascular disease have utilized multi-delay ASL approaches to correct CBF values for arrival time [56][57][58]. It was demonstrated that the multi-delay ASL technique holds an advantage for clinical applications, particularly for patients with arterial transit time abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a significant CVR impairment in patients with MMD, based on ASL MRI and PET measurements following the injection of vasodilator acetazolamide ( Deckers et al, 2021 ; Zhao et al, 2022 ). These studies showed that the CBF of patients with MMD did not increase after the injection of acetazolamide, suggesting that the cerebral vessels were already at maximal vasodilation to compensate for CBF reduction.…”
Section: Vascular Smooth Muscle Cell Dysfunction and Cerebrovascular ...mentioning
confidence: 99%
“…Even where they have been compared to SPECT and PET, their predictive value regarding the clinical course of the disease have not yet been prospectively verified. [82][83][84][85]…”
Section: Paediatric Patientsmentioning
confidence: 99%